Ion Transport, Current–noise in Nanopores and Conical Nanopores - VR Vishal, Nandigana (Annals of Mathematics and Physics, 2025)
Abstract In this paper, we build an ion transport model that requires less computational cost. We study the ion transport firstly in conical nanopores. We study the current-time in conical nanopores. The noise is modelled in our study. The noise in conical nanopores is due to the pore diameter and salt concentration. We consider 1 M KCl. We extend our study to understand the current time in nanopores. We consider the graphene nanopores. The noise in our nanopores model is due to the pore diameter only. We consider 1 M KCl. We study the influence of ion transport from the conductance relation to concentration for the solid-state nanopores. The concentrations studied are 0.003 M, 0.01 M, 0.03 M, 0.05 M, 0.15 M, 0.3 M, 0.4 M, 0.5 M, and 1 M KCl. We study the linear current-voltage characteristics for solid-state nanopores. We consider 1 M KCl. The study of nanofluidics can find applications in energy, water desalination, and neuromorphic computing devices.